Experimental Analysis of Voice and Data Transmission Parameters for Mobile Terminals in Cellular Data Networks - Jiménez-Licea, Montserrat; Vidal-Beltrán, Sergio; López-Bonilla, José L. (Scientific Research Publishing, 2011)
This work presents the experimental results related to performance measurements in GSM and GPRS cellular data networks. Two Mobile Terminals were used, in order to take place the scenario. Power Level, Power vs Time, Modula-tion Analysis, Modulation Spectrum, (BER) Bit Error Rate and Throughput were considered in this analysis.
Keywords: GSM; GPRS; Cellular Networks